New York City’s Beloved Owl: Review of Finding Flaco (2024) by Jacqueline Emery and David Lei - May, Talitha (Humanimalia, 2025)
Review of:Jacqueline Emery and David Lei, Finding Flaco: Our Year with New York City’s Beloved Owl. Foreword by Ed Shanahan. Afterword by Rita McMahon. New York: Owls of New York, 2024. 224 pp. $50.00 (hb).